INFORMATION MANAGEMENT: COMMUNICATION SECURITY STRATEGY OF SMALL AND MEDIUM BUSINESS - Пригодюк, Олена; Парніков, Ілля (SWorldJournal, 2024)
The article examines the role and significance of modern Ukrainian MSB, which forms strategic plans regarding the possibility of communication support in today’s conditions. An analysis of the activities of small and medium-sized businesses in pre-war Uk